New approach to the approximation of «dose – effect» dependence during the human somatic cells irradiation - V. F. Chekhun; E. A. Dyomina; M. O. Druzhyna; A. N. Kalinkevich; M. O. Zhovner; S. O. Vershynsky; V. Yu. Storizhko (Ядерна фізика та енергетика)
New data on cytogenetic approximation of the experimental cytogenetic dependence "dose - effect" based on the spline regression model that improves biological dosimetry of human radiological exposure were received. This is achieved by reducing the error of the determination of absorbed dose as compared to the traditional use of linear and linear-quadratic models and makes it possible to predict the effect of dose curves on plateau.